ANALISIS PENANGGULANGAN DAN PEREDARAN NARKOBA TERHADAP GENERASI MUDA DILINGKUNGAN HUKUM POLRES KARAWANG - Harries Madiistriyatno; Marsono Marsono; Feriandy Feriandy (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
The objectives of this study are: 1) To determine the effect of countermeasures against the younger generationwithin the legal environment of the Karawang Police. 2) To determine the effect of drug trafficking on the youngergeneration within the Karawang Police District. 3) To find out the effect of joint control and distribution of drugs onthe younger generation in the Karawang Police legal environment.“This research approach is quantitative, descriptiveand associative. The population in this study were 120 young people in the Karawang Police District. Regarding theresearch, the author uses the Slovin technique. So the number of samples studied were 54 respondents, namely theyounger generation in the Karawang Police District.“The results of this study indicate that: 1) There is an effect oftackling the younger generation, as evidenced by the ttable value for n = 54 of 2,005. So 4.786 2,005, then H0 isrejected and Ha is accepted, it can be stated that Countermeasures (X1) have a significant effect on the YoungGeneration The younger generation (Y). 2) There is an influence of Drug Circulation with the Young Generation, itis proven that the ttable value for n = 54 is 2,005. So 9,693 2,005, then H0 is rejected and Ha is accepted, it can beconcluded that partially the Drug Circulation variable (X2) affects the Young Generation The younger generation(Y). 3) There is a joint effect of Drug Control and Circulation on the Young Generation, as evidenced by the Fcountvalue of 105,320, while Ftable (a 0.05) for n = 54 is 2.78. So Fcount from Ftable (a 0.05) or 105.320 2.78 witha significant level of 0.000 because 0.000 0.05, it can be said that Countermeasures (X1) and Drug Circulation(X2) are jointly positively related to the Young Generation (Y). While the R value is 0.805. This shows that 80.5% ofCountermeasures (X1) and Drug Circulation (X2) are simultaneously related to the Young Generation (Y), while theremaining 19.5% are related to other factors not examined in this study.“